CREDIT LIBERALIZATION REFORM: A SIMPLE MODEL - VASILEV, Aleksandar (Theoretical and Practical Research in Economic Fields, 2022)
This note presents a simple setup of credit liberalization. We find that the effect is not uniform but depends on the level of GDP. In other words, the model predicts that richer countries benefit more than poor countries from opening up their capital account. This finding has important policy implications, as it suggests that developing economies should be cautious when it comes to the liberalization of their capital account.